Storage Systems are Distributed Systems (So Verify Them That Way!) - Hance, Travis; Lattuada, Andrea; Hawblitzel, Chris; Howell, Jon; Johnson, Rob; Parno, Bryan (Operating Systems Design and Implementation (OSDI), 2020)
To verify distributed systems, prior work introduced a methodology for verifying both the code running on individual machines and the correctness of the overall system when those machines interact via an asynchronous distributed environment. The methodology requires neither domain-specific logic nor tooling. However, distributed systems are only one instance of the more general phenomenon of systems code that interacts with an asynchronous environment. We argue that the software of a storage system can (and should!) be viewed similarly. We evaluate this approach in VeriBetrKV, a key-value store based on a state-of-the-art Bεtree. In building VeriBetrKV, we introduce new techniques to scale automated verification to larger code bases, still without introducing domain-specific logic or tooling. In particular, we show a discipline that keeps the automated verification development cycle responsive. We also combine linear types with dynamic frames to relieve the programmer from most heap-reasoning obligations while enabling them to break out of the linear type system when needed. VeriBetrKV exhibits similar query performance to unverified databases. Its insertion performance is 24× faster than unverified BerkeleyDB and 8× slower than RocksDB.